2018
DOI: 10.1097/mpg.0000000000001812
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Amino Acid Analysis Can Discriminate De Novo Treatment‐Naïve Pediatric Inflammatory Bowel Disease From Controls

Abstract: Significantly increased levels of six different fecal amino acids were found in patients with IBD compared to controls. Whether these differences reflect decreased absorption or increased loss by inflamed intestines needs to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 38 publications
7
36
0
Order By: Relevance
“…No specific role is yet reported for alanine. Whether these differences reflect decreased absorption or increased loss by inflamed intestines needs to be elucidated, but is consistent with previous findings on pediatric IBD patients (Bosch et al, 2018).…”
Section: Fecal Metabolomic Analysis Can Serve As a Diagnostic And Prosupporting
confidence: 89%
“…No specific role is yet reported for alanine. Whether these differences reflect decreased absorption or increased loss by inflamed intestines needs to be elucidated, but is consistent with previous findings on pediatric IBD patients (Bosch et al, 2018).…”
Section: Fecal Metabolomic Analysis Can Serve As a Diagnostic And Prosupporting
confidence: 89%
“…Phenylalanine was identified as a major fecal metabolite in IBS, and phenylalanine metabolism was the most relevant pathway influenced by IBS . Phenylalanine is liphophilic and aromatic amino acid which influence membrane diffusion and transportation . A previous study showed that phenylalanine increase membrane permeability.…”
Section: Discussionmentioning
confidence: 99%
“…This scenario is highly similar to other chronic inflammatory diseases (eg, rheumatoid arthritis 3 or the metabolic inflammation seen in obesity 4 ), where no intestinal leakage or malabsorption is expected. Second, in the study by Lamas et al in adult patients with IBD, a highly significant decrease of fecal TRP levels was observed, 5 which may represent a difference between adults and the pediatric patients investigated by Bosch et al 2 We value the thoughts of Bosch et al regarding the relationship between interleukin (IL)-22 levels and TRP metabolites. Indeed, we were able to confirm elevated IL-22 concentrations in active IBD, as previously reported.…”
mentioning
confidence: 92%
“…Bosch et al have recently extended our observation of low systemic tryptophan (TRP) levels in inflammatory bowel disease (IBD) 1 by showing increased levels of TRP and 4 other aromatic amino acids in the stools of 30 pediatric patients with IBD. 2 They suggested a disturbed host-microbiota interaction as a mechanism. In their letter, they propose that colonic leakage and malabsorption rather than increased metabolism may explain the lowered systemic TRP levels in patients with IBD.…”
mentioning
confidence: 99%
See 1 more Smart Citation